2016
DOI: 10.4236/ojg.2016.69085
|View full text |Cite
|
Sign up to set email alerts
|

Dolomitization Mechanism Based on Petrography and Geochemistry in the Shotori Formation (Middle Triassic), Central Iran

Abstract: Middle Triassic carbonate sequences of Shotori Formation have a thickness of 70 m and are deposited Robat-e-Kalmard region of Tabas city in Central Iran basin. Gradationally and conformably overlying Sorkh shale Formation, Shotori Formation, mostly composed of medium to thick dolomites (50 m), interbeded with thin lime and sandstones, is disconformable by a laterite horizon at its upper boundary. This Formation mainly consists of fine-to-coarsely crystalline dolomites. According to petrographic (fabric and gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…2). This is common in carbonate platforms, with various models available to explain the systematic distribution of dolomite and limestone (Rahimi et al 2016). A terrestrial source of high-Mg waters is favoured in this case, which promoted dolomitization of limestone close to shore and/or close to the unconformity.…”
Section: Dj Wentmentioning
confidence: 93%
See 1 more Smart Citation
“…2). This is common in carbonate platforms, with various models available to explain the systematic distribution of dolomite and limestone (Rahimi et al 2016). A terrestrial source of high-Mg waters is favoured in this case, which promoted dolomitization of limestone close to shore and/or close to the unconformity.…”
Section: Dj Wentmentioning
confidence: 93%
“…A terrestrial source of high-Mg waters is favoured in this case, which promoted dolomitization of limestone close to shore and/or close to the unconformity. Dolomitization is interpreted to have occurred during early diagenesis and shallow burial as high-Mg meteoric pore waters mixed with those of marine phreatic origin (Humphrey & Quinn, 1989;Rahimi et al 2016).…”
Section: Dj Wentmentioning
confidence: 99%
“…Interestingly, a nanoscale in-situ observation using atomic force microscopy (AFM) has shown that the precipitation of gypsum is coupled with dolomite dissolution 59 . The absence of fossils in MV1 can be related to dolomitization in the upper tidal flat environment 60 . MV1 is possibly a re-worked carbonate material from the vents during sediment extrusion thereby abrading pre-existing earlier dolomite of spheroidal nature.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, hypersaline fluids, usually produced by high rates of evaporation, resulting in the precipitation of dolomites along with gypsum and anhydrite (Mckenzie, 1981). During petrographic examinations, fine crystalline dolomite (Df) exhibited small crystal size and planar intercrystalline boundaries with fabric retentive character are the possibilities of the dolomites formed in supratidal and intertidal realms in the early stage of diagenesis near-surface lowtemperature conditions (Figure 3a-d;Saller, 1984;Gregg and Sibley, 1984;Land, 1985;Sibley and Gregg, 1987;Mitchell et al, 1987;Gregg and Shelton, 1990;Rahimi et al, 2016). According to Shah, (2009) the epeirogenesis experienced resultant emergence in various areas of Pakistan, and this caused unconformities of varying magnitude.…”
Section: Discussionmentioning
confidence: 99%